Methods for synthesis of matching circuits for broadband radio devices with unstable load impedance - I. A. Dubovik; P. V. Boykachev; V. O. Isaev; A. A. Dmitrenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2021)
The aim of this work is to select a synthesis method for a broadband matching circuit that provides maximum power transfer from a signal source to a load in the presence of a changing load impedance of a radio engineering device. To achieve this goal, an analysis of the main directions of designing broadband matching circuits (analytical, numerical, graphic-analytical synthesis methods) was carried out. Based on the results of a comparison of synthesis methods, their features (advantages and disadvantages) were indicated. The analysis of methods of synthesis of broadband matching circuits was carried out. For the analysis, the generalized Darlington method, the method of real frequencies, the structural-parametric synthesis method based on the T-matrix apparatus, and the graphic-analytical method based on the Volpert-Smith diagram were chosen). Using these synthesis methods, broadband matching circuits were obtained for various types of loads. Comparison of the results obtained was carried out according to several indicators: the level of the power transfer coefficient in the operating frequency range, the sensitivity of the power transfer coefficient to the change in the ratings of the elements of the matching circuit and the load impedance, provided that the number of elements of the matching circuit is no more than six. Based on the comparison and analysis, it was found that the most preferable synthesis method for solving the problem posed is the method of real frequencies. Its advantage is the use of a combination approach (iterative determination of the parameters of the resistance function with an analytical representation of the transfer function). Matching circuits obtained using this synthesis method provided the highest level of power transmission coefficient, as well as the lowest sensitivity value in a given frequency band for the considered types of loads.